Human cancer, the naked mole rat and faunal turnovers - Anders Bredberg (Cancer Medicine, 2019)
Abstract We argue that the human evolutionary heritage with frequent adaptations through geological time to environmental change has affected a trade‐off between offspring variability and cancer resistance, and thus favored cancer‐prone individuals. We turn the attention to a factor setting the highly cancer‐resistant naked mole rat apart from most other mammals: it has remained phenotypically largely unchanged since 30‐50 million years ago. Research focusing on DNA stability mechanisms in ‘living fossil’ animals may help us find tools for cancer prevention and treatment.